Single-cell transcriptomic analyses provide insights into the developmental origins of neuroblastoma - Jansky, Selina; Sharma, Ashwini Kumar; Körber, Verena; Quintero, Andrés; Toprak, Umut; Wecht, Elisa M.; Gartlgruber, Moritz; Greco, Alessandro; Chomsky, Elad; Grünewald, Thomas G. P.; Henrich, Kai-Oliver; Tanay, Amos; et al. (Nature genetics, 2021)
Neuroblastoma is a pediatric tumor of the developing sympathetic nervous system. However, the cellular origin of neuroblastoma has yet to be defined. Here we studied the single-cell transcriptomes of neuroblastomas and normal human developing adrenal glands at various stages of embryonic and fetal development. We defined normal differentiation trajectories from Schwann cell precursors over intermediate states to neuroblasts or chromaffin cells and showed that neuroblastomas transcriptionally resemble normal fetal adrenal neuroblasts. Importantly, neuroblastomas with varying clinical phenotypes matched different temporal states along normal neuroblast differentiation trajectories, with the degree of differentiation corresponding to clinical prognosis. Our work highlights the roles of oncogenic MYCN and loss of TFAP2B in blocking differentiation and may provide the basis for designing therapeutic interventions to overcome differentiation blocks.
Das PDF enthält zusätzlich einen Anhang von 19 Seiten
Gesehen am 26.03.2021